IMPLEMENTASI PEMBELAJARAN SIKLUS AIR MELALUI PENDAYAGUNAAN ALAT PERAGA PADA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 6 BANDA ACEH - jurta, Jurtawani (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
The problem addressed in this study is the persistent lack of student achievement in understanding the water cycle material. The research objective is to examine the role of instructional aids on students' learning outcomes regarding the water cycle material in the science class of fifth grade at MIN 6 Banda Aceh. The research design employed is a pre-experimental design in the form of Pretest and Posttest, which is an experiment involving only one class as the experimental group without a control group. The subjects of this study were 39 fifth-grade students, and data collection methods used were tests and observation sheets. Data analysis was conducted by comparing students' scores from the test results with the Minimum Completeness Criteria (MCC) set by the school, which is 80. The results indicate that the use of instructional aids can enhance learning outcomes in the water cycle material. This is evidenced by the increase in the number of students who meet the MCC from pre-cycle to cycle II. In cycle I, there were still 12 students who did not achieve the MCC. Understanding the material and concepts of the water cycle with the use of instructional aids showed better learning outcomes compared to before using them. Therefore, it can be recommended that instructional aids be used as an alternative learning media in science education.